UNILATERAL UTERINE TORSION SECONDARY TO PYOMETRA IN A BITCH - MURUGAVEL, K; ANTOINE, D; KANTHARAJ, S; RAJU, M S (The Indian Journal of Animal Reproduction, 2023)
Successful surgical management of unilateral uterine torsion secondary to pyometra in a bitch is discussed.